Viewing art through information visualization: A case study of bob ross's the joy of painting. Issue 1 (2014) - Graten, Erienne; Hall, Andrea; Hall, Elaine; Chen, H. Michelle
ABSTRACT: This poster examines data about 403 images that appeared on Bob Ross's PBS series, The Joy of Painting . We analyzed a set of 3324 tags that described his artistic output ‐ . Looking at this set of data suggests more complex themes‐emotion, memory, and the act of painting itself‐ underlie Ross's landscapes. It presents a model for considering other artists with large oeuvre and large image sets. With digitization, information professionals have often considered how to construct metadata, tags, and controlled vocabularies to make images searchable. Less frequently have they considered how researchers might use those classification systems, quantitative data derived from them, and visualizations of them to assess an artist or historical period's visual culture. Using Bob Ross as a case study, we utilized information visualization techniques to analyze the contents of artwork through the trajectory of artistic creation.